Teaching English in Pesantren: The Dynamics of Code-Switching in Multilingual Classrooms - Fitriyah, Nailiyatul; Hidayat, Didin Nuruddin; Husna, Nida (Fakultas Sastra - Universitas Muslim Indonesia, 2025)
While the role of code-switching in multilingual classrooms has been widely examined in previous studies, particularly in general educational settings, only a limited number of investigations have focused on its application to pesantren settings teaching religious and secular subjects concurrently. This study investigates the use of code-switching in English teaching at a pesantren or Islamic boarding school in East Ciputat. The research found that code-switching is strategically used to explain vocabulary, check understanding, summarize lessons, and provide feedback. It was found that during complex content delivery and reflective activities, code-switching was more frequent, simplifying challenging material. Students generally showed positive reactions, but occasional confusion was observed. The study also found that other teaching styles, such as group discussions and multimedia use, further complemented code-switching. The study suggests that while code-switching enhances comprehension, teachers must strike a balance to avoid over-reliance on the native language, promoting more immersive English language learning. It calls for continued professional development for teachers in multilingual environments to optimize code-switching strategies and support students' language proficiency growth.